1981
DOI: 10.1203/00006450-198104001-01292
|View full text |Cite
|
Sign up to set email alerts
|

1264 Afterload Reduction by Sodium Nitroprussiate (Snp) in Asphyxiated Infants With Hypertension and Heart Failure

Abstract: Extreme similarities in the anatomy and physiology of the feto-placento-uterine unit in baboons and humans make the baboon an ideal model to investigate various aspects of reproductive physiology. Thirty-six amniotic fluid samples from 30 normal baboon pregnancies ranging in length from 50 to 173 days (term=180 days) were analyzed to obtain baseline data.Amniotic fluid volume as determined by para-aminohippurate dilution ranged from 126 to 380 ml, with a mean ( ' S D ) of 269'77.6 ml. Volume did not vary sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sodium nitroprusside is a potent, direct-acting vasodilator which has been used for systemic hypertension (16), pulmonary hypertension (7), and congestive heart failure (6,17). Although experience with nitroprusside in the neonate is limited, two case reports (1,4) have suggested that nitroprusside may have a therapeutic role in decreasing the high pulmonary vascular resistance of hyaline membrane disease.…”
mentioning
confidence: 99%
“…Sodium nitroprusside is a potent, direct-acting vasodilator which has been used for systemic hypertension (16), pulmonary hypertension (7), and congestive heart failure (6,17). Although experience with nitroprusside in the neonate is limited, two case reports (1,4) have suggested that nitroprusside may have a therapeutic role in decreasing the high pulmonary vascular resistance of hyaline membrane disease.…”
mentioning
confidence: 99%